2013
DOI: 10.2527/jas.2013-6421
|View full text |Cite
|
Sign up to set email alerts
|

Effect of moderate dietary restriction on visceral organ weight, hepatic oxygen consumption, and metabolic proteins associated with energy balance in mature pregnant beef cows1,2

Abstract: Twenty-two nonlactating multiparous pregnant beef cows (639 ± 68 kg) were used to investigate the effect of dietary restriction on the abundance of selected proteins regulating cellular energy metabolism. Cows were fed at either 85% (n = 11; LOW) or 140% (n = 11; HIGH) of total NE requirements. The diet consisted of a haylage-based total mixed ration containing 20% wheat straw. Cows were slaughtered by block (predicted date of parturition), beginning 83 d after the initiation of dietary treatments and every we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 55 publications
2
18
0
Order By: Relevance
“…In dairy cattle, several studies have evaluated the effects of different physiological stages (prepartum, early lactation, and late lactation), different diets for heifers, and days relative to calving on organ mass (Andrew et al, 1994;Moallem et al, 2004;Reynolds et al, 2004). In beef cows, Wood et al (2013) did not observe a difference in lung mass between cows that were fed at 85 and 140% of their nutritional requirements. According to Cesta (2006), the 3 main factors that affect spleen development are species, age, and genetic composition.…”
Section: Feeding Regimenmentioning
confidence: 93%
See 1 more Smart Citation
“…In dairy cattle, several studies have evaluated the effects of different physiological stages (prepartum, early lactation, and late lactation), different diets for heifers, and days relative to calving on organ mass (Andrew et al, 1994;Moallem et al, 2004;Reynolds et al, 2004). In beef cows, Wood et al (2013) did not observe a difference in lung mass between cows that were fed at 85 and 140% of their nutritional requirements. According to Cesta (2006), the 3 main factors that affect spleen development are species, age, and genetic composition.…”
Section: Feeding Regimenmentioning
confidence: 93%
“…However, we demonstrated in this study that FR also influences spleen mass. Wood et al (2013) demonstrated a greater rumen mass in cows that were fed 140% of their nutrient energy requirements compared with those fed 85%. According to those authors, this may be due to greater rumen fill, which could influence rumen mass.…”
Section: Feeding Regimenmentioning
confidence: 93%
“…The experiments were approved by the University of Guelph Animal Care Committee and the animals were cared for according to the guidelines of the Canadian Council of Animal Care (1993). Animal care and experimental design were described previously (Wood et al 2013a(Wood et al , 2013b.…”
Section: Animal Management and Treatmentsmentioning
confidence: 99%
“…For experiment 2 (Wood et al 2013a), 22 (11 per dietary treatment) nonlactating, mature pregnant beef cows, primarily of Angus and Simmental crossbreeding were used in a randomized complete block design. Each block (n = 5 or 6) was slaughtered approximately 4 wk before expected date of parturition (approximately 250 d of gestation).…”
Section: Animal Management and Treatmentsmentioning
confidence: 99%
“…Perhaps, these changes occur to adjust to the restricted amount of available nutrients to maintain BW (Ferrell et al, 1986;Burrin et al, 1989). Research in pregnant cows fed at either 85% or 140% of NE requirments indicated that cows fed at the lower NE intake level from mid-gestation until day 250 had decreased hepatic in vitro O 2 consumption per gram protein or relative to BW but hepatic weight did not differ between treatments (Wood et al, 2013). This may indicate nutrient restriction later in gestation may have different effects than during early or mid-gestation.…”
Section: In Sheepmentioning
confidence: 99%